A new species and record of Aceria (Acari: Prostigmata: Eriophyoidea) on Carlina spp. (Asteraceae) from Serbia - Vidović, Biljana (Zootaxa, 2014)
A new species of eriophyoid mite, Aceria utzkae n. sp., inhabiting Carlina acanthifolia subsp. utzka (Hacq.) Meusel & Kästner (Asteraceae) is described and illustrated. It is compared with Aceria carlinae (Nalepa), the only other species known to inhabit Carlina spp., and a differential diagnosis is provided. Both species are recorded from Serbia for the first time and a new host plant, Carlina vulgaris (Asteraceae) L., is also documented for Aceria carlinae.